Effects of ion composition on escape and morphology on Mars - Q. Zhang; Q. Zhang; M. Holmström; X.-D. Wang (Annales Geophysicae, 2023)
We refine a recently presented method to estimate ion escape from non-magnetized planets and apply it to Mars. The method combines in situ observations and a hybrid plasma model (ions as particles, electrons as a fluid). We use measurements from the Mars Atmosphere and Volatile Evolution (MAVEN) mission and Mars Express (MEX) for one orbit on 1 March 2015. Observed upstream solar-wind conditions are used as input to the model. We then vary the total ionospheric ion upflux until the solution fits the observed bow shock location. This solution is a self-consistent approximation of the global Mars–solar-wind interaction at the time of the bow shock crossing for the given upstream conditions. We can then study global properties, such as the heavy-ion escape rate. Here, we investigate in a case study the effects on escape estimates of assumed ionospheric ion composition, solar-wind alpha-particle concentration and temperature, solar-wind velocity aberration, and solar-wind electron temperature. We also study the amount of escape in the ion plume and in the tail of the planet. Here, we find that estimates of total heavy-ion escape are not very sensitive to the composition of the heavy ions or to the number and temperature of the solar-wind alpha particles. We also find that velocity aberration has a minor influence on escape but that it is sensitive to the solar-wind electron temperature. The plume escape is found to contribute 29 % of the total heavy-ion escape, in agreement with observations. Heavier ions have a larger fraction of escape in the plume compared to the tail. We also find that the escape estimates scale inversely with the square root of the atomic mass of the escaping ion species.